European Human Resource Management: Researching developments over time - Wolfgang Mayrhofer; Chris Brewster (Management Revue, 2005)
This paper uses insights and data gained from 15 years of involvement in a research network studying HRM developments in Europe to explore the notion of 'European HRM' and the meanings of convergence and divergence in HRM Using data from the last decade of the Cranet research, the paper puts forward a more nuanced view of the notions of convergence and divergence, finding evidence of directional convergence, but little evidence of final convergence: whilst there are trends which point in similar directions, national differences remain a key factor in HRM.
Keywords: 650; Human Resource Management; European Human Resource Management; comparative research; convergence; Personalmanagement; Organisationsforschung; EU-Staaten